Optimization and kinetic study of lipase-catalyzed synthesis of palm-based kojic acid ester - Ashari, Siti Efliza (2013)
Palm-based kojic acid ester was produced through lipase-catalyzed esterification of kojic acid with oleic acid using lipase as a catalyst. The chemical and physical characterization of pure palm-based kojic acid ester was analyzed in order to be effectively applied in cosmetic application. The chemical characterization was determined by Fourier-Transform Infrared spectroscopy, Gas Chromatography- Flame Ionization Detector and Nuclear Magnetic Resonance in order to verify and elucidate the structure of product. It was found that kojic acid was esterified at C-5 position to produce palm-based kojic acid ester and the chemical’s name was (E)-6-(hydroxymethyl)-4-oxo-4H-pyran-3-yloctadec-9-enoate. The important physicochemical property of the ester such as skin irritancy test was found to be non-irritating with Human Irritancy Equivalent (HIE) score between 0.55-0.83. Response Surface Methodology and 5-level-4-factor central composite rotatable design were employed in optimizing the synthesis of palm-based kojic acid ester catalyzed by immobilized lipase from Rhizomucor meihei (Lipozyme RM IM) in acetonitrile. Four parameters such as temperature (°C), amount of enzyme (g), substrate molar ratio (kojic acid: oleic acid) and reaction time (h) were studied and their interaction effects were investigated. The optimized reaction conditions obtained after analysis with backward elimination are 0.17 g of enzyme and molar ratio of substrates (OA:KA) corresponding to 1:4 at 52.50°C for 42 h of reaction. Under this condition, the percentage yield of palm-based kojic acid ester produced was 37.2%. The improvement of the synthesis process was carried out in a 2 L stirred-tank reactor (STR) equipped with a multi-impeller design. The types of impeller used were Rushton Turbine (RT), High Efficiency (HE) and Half-pitched Helical Ribbon (HR). The configuration of HE-RT combination showed the highest conversion yield with 77.20% as compared to RT-HE (72.45%) and HR (63.68%). The high Reynolds Number, NRE (3463.89) was achieved at 250 rev/min using HR, which exhibits a transition flow pattern. The production of palm-based kojic acid ester in a 2 L stirred-tank reactor follows Newton’s Law due to the linear relationship in between the shear stress and shear rate. A heterogenous enzyme particles suspension was obtained at 250 rev/min and 30 mm of distance in between the two impellers (RT-HE). A kinetic study, using the experimental data obtained from the batch-mode of 2 L stirred-tank reactor was evaluated for the synthesis of palm-based kojic acid ester. This study was aimed to develop a kinetic model by focusing on the substrates concentration. Different acid and alcohol concentrations were tested systematically and the results were used to identify the best reaction scheme to describe the results obtained over an extended range of conditions. As a result, the kinetic of the reaction can be described by Ping-Pong Bi-Bi mechanism with acid inhibition (palm-based oleic acid). The values of the apparent kinetic parameters were estimated by non-linear regression analysis and computed as: υmax: 4.58 x 10 mmol/L.h.g; Km(KA): 1.87 x 10-7 mmol/L.h.g; Km(OA): 8.31 x 102 mmol/L.h.g ; Ki(OA): 5.32 x 106 mmol/L.h.g. A good agreement between the calculated and the observed value was found. Lipase-catalyzed esterification in a solvent-free system using Novozym 435 lipase was also investigated as a method for kinetic modeling of palm-based kojic acid ester. The structure of palm-based kojic acid ester was also elucidated. It was found that kojic acid was easily esterified at C-7 position to produce palm-based kojic acid ester and the chemical’s name was found to be (E)-(5-hydroxy-4-oxo-4H-pyran-2-yl)methyl octadec-9-enoate. The rate expression of this ester was developed using irreversible second-order power model as a first approach. The activation energy (Ea) shows a value of 7.90 x 104 J/mol and the kinetic reaction constant (ko) of 5.30 x 108 L.mol-1.min-1.gCAT -1. The adsorption value (KKAE) of 1.90 x 10-17 gCAT .gKAE -1 between catalyst and ester was correlated with the Langmuir-Hinshelwood-Hougen-Watson model as a second approach. The Gibbs energy, enthalpy and entropy changes for reaction at different temperature were calculated from the measured equilibrium constant using the integrated Van’t Hoff’s equation. The calculated values for the thermodynamic quantities of Gibbs energy, enthalpy and entropy changes are 2.77 x 104 J/mol, 9.85 x 105 J/mol and 4.77 x 102 J/mol.K, respectively.